The staff perspectives of facilitators and barriers to implementing virtual reality for people living with dementia in long-term care - Wong, Joey; Wong, Karen Lok Yi; Kan, Winnie; Wu, Catherine; Upreti, Mona; Van, Mary; Temirova, Alisha; Alfares, Hadil; Wen, Kayla; Sharma, Vaishali; Wallsworth, Christine; Mann, Jim; et al. (Frontiers in Dementia, 2024)
One emerging technology in long-term care (LTC) is virtual reality (VR), an innovative tool that uses head-mounted devices to provide the viewer with an immersive experience. It has been shown that VR has a positive impact on the well-being of residents living with dementia, and staff are essential in the implementation and sustainable use of technology. Currently, there is a lack of inclusion and focus on direct staff perspectives on VR implementation in LTC. This paper aims to report staff perspectives on VR adoption in a two-year study on a virtual reality program at three Canadian LTC homes. Our interdisciplinary team (clinicians, people living with dementia and family partners, trainees, and researchers) explored the facilitators and barriers to implementing VR in LTC, guided by the Consolidated Framework for Implementation Research (CFIR) and intersectionality supplemented CFIR. Twenty-one participants were recruited, including recreation staff, care aides, nurses, screeners, and leadership team members. The team collected data through staff interviews, focus groups, and ethnographic observation field notes. Reflexive thematic analysis was performed to identify themes reporting the facilitators and barriers for VR implementation in LTC from staff perspectives. The data analysis resulted in three facilitators and four barriers. Facilitators are 1) perceived VR benefits, 2) integrate VR into workflow and routines, and 3) partner with skillful VR champions. Barriers include 1) staff concerns about VR use, 2) financial burden and competing priorities, 3) lack of infrastructure and physical spaces, and 4) staff workload and limited leadership support. This study contributes to the field with staff perspectives on facilitators and barriers to VR implementation. It underscores the rarely discussed aspects of VR implementation, such as funding prioritization and implementation timing. We offer practical strategies to inform future practices and research. Future studies should further explore long-term VR implementation, the involvement of family members as VR facilitators, and the use of VR in LTC.